Identification of a female spawn‐associated Kazal‐type inhibitor from the tropical abalone Haliotis asinina. (July 2016) - Wang, Tianfang; Nuurai, Parinyaporn; McDougall, Carmel; York, Patrick S.; Bose, Utpal; Degnan, Bernard M.; Cummins, Scott F.
Abstract : Abalone ( Haliotis ) undergoes a period of reproductive maturation, followed by the synchronous release of gametes, called broadcast spawning. Field and laboratory studies have shown that the tropical species Haliotis asinina undergoes a two‐week spawning cycle, thus providing an excellent opportunity to investigate the presence of endogenous spawning‐associated peptides. In female H. asinina, we have isolated a peptide (5145 Da) whose relative abundance in hemolymph increases substantially just prior to spawning and is still detected using reverse‐phase high‐performance liquid chromatography chromatograms up to 1‐day post‐spawn. We have isolated this peptide from female hemolymph as well as samples prepared from the gravid female gonad, and demonstrated through comparative sequence analysis that it contains features characteristic of Kazal‐type proteinase inhibitors (KPIs). Has‐KPI is expressed specifically within the gonad of adult females. A recombinant Has‐KPI was generated using a yeast expression system. The recombinant Has‐KPI does not induce premature spawning of female H. asinina when administered intramuscularly. However it displays homomeric aggregations and interaction with at least one mollusc‐type neuropeptide (LRDFVamide), suggesting a role for it in regulating neuropeptide endocrine communication. This research provides new understanding of a peptide that can regulate reproductive processes in female abalone, which has the potential to lead to the development of greater control over abalone spawning. The findings also highlight the need to further explore abalone reproduction to clearly define a role for novel spawning‐associated peptide in sexual maturation and spawning. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Abalone has separate sexes that broadcast spawn gametes at periods influenced by temperature, tides, and endogenous cues. A peptide was identified in female abalone (Haliotis asinina) that is relatively abundant in hemolymph at egg spawning and exhibits some similarity with Kazal‐type inhibitors. It is exclusive to females where it is produced in that gonads and can interact with neuropeptides, possibly regulating their function. The findings highlight the need to explore abalone reproduction to clearly define endogenous cues for spawning.